Pengaruh Persepsi Keadilan Pajak, Kemudahan Pajak, dan Modernisasi Sistem Perpajakan terhadap Kepatuhan Penerapan Kebijakan Atas Pmk86/03/2020 Wajib Pajak UMKM - Uum Helmina; Nur Anita Chandra Putry (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study was conducted to determine the effect of perceptions of tax justice, perceptions of tax convenience, and modernization of the taxation system on compliance with the implementation of PMK 86/03/2020 MSME Taxpayers. The Covid-19 pandemic has caused the Indonesian economy to weaken greatly, one of which is the MSME sector. It is hoped that the existence of tax incentives for MSMEs borne by the government can help revive the current MSME sector. However, the size of MSME actors is not the same as compared to the MSME actors' tax compliance which is still low in reporting their taxes, this is because the Directorate General of Taxes (DGT) focuses more on large taxpayers while supervision of MSME actors has not been carried out optimally. This research is quantitative using primary data. The sample in this study was SMEs in the Special Region of Yogyakarta. This researcher uses an instrument in the form of a questionnaire. The data processing technique used is multiple linear regression with the help of SPSS. The results of the study indicate that the perception of tax convenience does not affect compliance with the application of policies on PMK /03/2020 MSME taxpayers. Perceptions of tax justice and the modernization of the taxation system on compliance with the implementation of policies on PMK 86/03/2020 MSME taxpayers have a positive influence.